Electrolyte and lithium ion battery
By using sulfhydryl ether compounds with specific structures in the lithium-ion battery electrolyte, the problem that lithium-ion batteries are difficult to take into account both high-temperature electrical performance and fast charging performance is solved, and the stability and safety of the battery under high temperature and fast charging conditions are achieved. Performance improvement.
Patent Information
- Application Number
- CN202411647930.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
It is difficult for existing lithium-ion batteries to take into account both excellent high-temperature electrical performance and fast charging performance.
The sulfur-heterogenic ether compound with a specific structure is used as the additive to the electrolyte solution. The Mn2+ ions are matched with the Mn2+ ions through the size of the sulfur-heterogenic ether cavity to form an S-Mn bond, stabilize the Mn2+ ions in the electrolyte, and form a stable complex at the positive electrode interface. inhibits the dissolution and migration of Mn2+ ions.
It achieves the improvement of the stability and circulation performance of lithium-ion batteries under high temperature and fast charging conditions, while reducing the gas production inside the battery and improving safety performance.
Smart Images

Figure CN119447460A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte and a lithium ion battery. Background Art
[0002] With the rapid development of power batteries and electrochemical energy storage, lithium-ion batteries are increasingly used in scalable energy storage devices, especially as a power source for new energy electric vehicles. However, with the rapid development of new energy vehicles, the performance requirements for lithium-ion batteries are gradually increasing, especially seeking lithium-ion batteries with higher energy density, high fast charging capability, high stability, and low-cost systems. This is the mainstream direction of lithium battery development. In order to meet the requirements of lithium battery development, the research on a new generation of positive electrode materials, lithium manganese iron phosphate (LMFP), has made rapid progress. In the process of developing fast-charging cells based on LMFP positive electrode materials, in order to meet the fast charging requirements of 3C and above, the electrolyte system is designed to have the characteristics of low viscosity and high ionic conductivity, which is achieved by increasing the proportion of low-viscosity solvents and using lithium salts with high ionic conductivity. However, these characteristics will cause the performance of the battery cell to deteriorate significantly under high-temperature cycles. The main reason is that the Mn in the positive electrode material 4+ A disproportionation reaction will occur, and Mn 2+ In the form of Mn, these dissolved transition metal ions will migrate and deposit on the surface of the graphite anode, destroying its solid electrolyte interface film (SEI). 2+ It also catalyzes PF6 - decomposition, generating PF5, which further leads to thermal decomposition of the electrolyte and serious gas generation. 2+ The catalytic effect of ions on electrolyte will play a significant role in the cycle performance and safety of the battery.
[0003] In summary, in the process of developing electrolytes for fast-charging cells based on LMFP positive electrode materials, selecting suitable additives and developing matching injection and formation methods are particularly critical for achieving fast charging of lithium batteries and long-term stable cycling at higher temperatures. Summary of the invention
[0004] The main purpose of the present invention is to provide an electrolyte and a lithium ion battery to solve the problem that lithium ion batteries in the prior art are difficult to simultaneously achieve excellent high temperature electrical performance and fast charging performance.
[0005] In order to achieve the above object, according to one aspect of the present invention, an electrolyte is provided, the electrolyte comprising an organic solvent, a lithium salt additive, LiPF6 and an additive, the additive comprising a crown ether compound, the crown ether compound comprising a structure shown in Formula I and Formula II,
[0006]
[0007] Wherein, L1, L2, L3 and L4 are each independently selected from any one of a single bond, a C1-C4 alkylene group and a phenylene group; R1, R2, R3 and R4 are each independently selected from any one of hydrogen, vinyl, amino, cyano, a C1-C4 alkyl group, a five-membered heterocyclic group, a phosphate group and -C(O)R, and R is selected from any one of hydrogen, a hydroxyl group and a C1-C4 alkyl group.
[0008] Further, and Each independently selected from hydrogen, methyl, ethyl, vinyl,
[0009]
[0010] Any one of .
[0011] Furthermore, the mass content of the crown ether compound is 1-10% of the total mass of the electrolyte.
[0012] Furthermore, the mass ratio of the crown ether compound with the structure represented by the above formula I to the crown ether compound with the structure represented by the above formula II is 5:1 to 1:1.
[0013] Furthermore, the lithium salt auxiliary agent is selected from any one or more of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium hexafluoroarsenate, perfluoroalkylsulfonylmethyl lithium and lithium bis(trifluoromethylsulfonyl)imide.
[0014] Furthermore, in terms of mass percentage, the electrolyte includes 1 to 10 wt % of a crown ether compound, 1 to 5 wt % of lithium bis(fluorosulfonyl)imide, 10 to 15 wt % of LiPF6, 0.5 to 2 wt % of vinyl sulfate and an organic solvent.
[0015] Furthermore, the above-mentioned organic solvent includes a first solvent and a second solvent, wherein the first solvent is a cyclic carbonate, and the second solvent is a chain carbonate and / or a carboxylate; preferably, the first solvent is propylene carbonate and / or ethylene carbonate; preferably, the second solvent is selected from any one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, propyl propionate, methyl acetate and γ-butyrolactone.
[0016] Furthermore, the mass ratio of the first solvent to the second solvent is 1:1-3.
[0017] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte is the electrolyte described above.
[0018] Furthermore, the positive electrode sheet includes a positive electrode material, and the positive electrode material is lithium manganese iron phosphate.
[0019] The technical solution of the present invention is applied, and the electrolyte in the present application uses a thiocrown ether compound with a specific structure as an additive, especially a crown ether compound with a structure shown in Formula I and Formula II, and the size of the thiocrown ether cavity is related to the Mn 2+ The sulfur atoms in the thiacrown ethers react with the manganese ions in the electrolyte to form S-Mn bonds, thereby reducing the Mn 2+ The energy barrier overcome when passing through the thiacrown ether ring cavity can not only stabilize the Mn 2+ ions, and can also react with Mn at the interface with the positive electrode. 2+ ions form a stable complex, thereby fundamentally inhibiting the Mn 2+ The ions dissolve and migrate to the negative electrode under high temperature and fast charging conditions, further reducing their damage to the SEI film. According to the hard-soft acid-base theory, the introduction of sulfur atoms can enhance the selective response of crown ether compounds to transition heavy metal ions, and the number of sulfur atoms in the crown ether compounds plays a decisive role in their selectivity. The size of the ring cavity of the crown ether compound also has a certain influence on the selectivity and sensitivity of the crown ether ring. Specifically, the crown ether compound shown in Formula I has two oxygen atoms and two sulfur atoms substituted, and the crown ether compound shown in Formula II has four sulfur atoms substituted. The two have ring cavities of similar size and can synergistically react with Mn with different valence states. 2+ With Mn 3+ ions match, so that the crown ether compound shown in formula I helps to improve the fast charging performance of lithium ion batteries, and the crown ether compound shown in formula II helps to improve the high temperature electrical performance of lithium ion batteries. Through the synergistic effect of the crown ether compounds of the above two structures, a lithium ion battery that can take into account both high temperature electrical performance and fast charging performance is obtained. In addition, the crown ether compound of the above structure allows it to be combined with Li + Ions maintain a certain distance and do not affect Li + The solvation structure of the battery will not reduce the ionic conductivity and fast charging performance of the battery. Therefore, the introduction of the crown ether compound is beneficial to improving the stability and cycle performance of lithium-ion batteries under high temperature and fast charging conditions, while also helping to reduce the gas production inside the battery, thereby improving the safety performance of lithium-ion batteries. DETAILED DESCRIPTION
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0021] As analyzed in the background art, it is difficult for lithium-ion batteries in the prior art to simultaneously achieve both excellent high-temperature electrical performance and fast charging performance. To solve this problem, the present invention provides an electrolyte and a lithium-ion battery.
[0022] In a typical embodiment of the present application, an electrolyte is provided, which includes an organic solvent, a lithium salt additive, LiPF6 and an additive, wherein the additive includes a crown ether compound, and the crown ether compound includes a structure shown in Formula I and Formula II:
[0023]
[0024] Wherein, L1, L2, L3 and L4 are each independently selected from any one of a single bond, a C1-C4 alkylene group and a phenylene group; R1, R2, R3 and R4 are each independently selected from any one of hydrogen, vinyl, amino, cyano, a C1-C4 alkyl group, a five-membered heterocyclic group, a phosphate group and -C(O)R, and R is selected from any one of hydrogen, a hydroxyl group and a C1-C4 alkyl group.
[0025] The electrolyte in the present application uses a thiocrown ether compound with a specific structure as an additive, especially a crown ether compound with a structure shown in Formula I and Formula II. 2+ The sulfur atoms in the thiacrown ethers react with the manganese ions in the electrolyte to form S-Mn bonds, thereby reducing the Mn 2+ The energy barrier overcome when passing through the thiacrown ether ring cavity can not only stabilize the Mn 2+ ions, and can also react with Mn at the interface with the positive electrode. 2+ ions form a stable complex, thereby fundamentally inhibiting the Mn 2+ The ions dissolve and migrate to the negative electrode under high temperature and fast charging conditions, further reducing their damage to the SEI film. According to the hard-soft acid-base theory, the introduction of sulfur atoms can enhance the selective response of crown ether compounds to transition heavy metal ions, and the number of sulfur atoms in the crown ether compounds plays a decisive role in their selectivity. The size of the ring cavity of the crown ether compound also has a certain influence on the selectivity and sensitivity of the crown ether ring. Specifically, the crown ether compound shown in Formula I has two oxygen atoms and two sulfur atoms substituted, and the crown ether compound shown in Formula II has four sulfur atoms substituted. The two have ring cavities of similar size and can synergistically react with Mn with different valence states. 2+ With Mn 3+ ions match, so that the crown ether compound shown in formula I helps to improve the fast charging performance of lithium ion batteries, and the crown ether compound shown in formula II helps to improve the high temperature electrical performance of lithium ion batteries. Through the synergistic effect of the crown ether compounds of the above two structures, a lithium ion battery that can take into account both high temperature electrical performance and fast charging performance is obtained. In addition, the crown ether compound of the above structure allows it to be combined with Li+ Ions maintain a certain distance and do not affect Li + The solvation structure of the battery will not reduce the ionic conductivity and fast charging performance of the battery. Therefore, the introduction of the crown ether compound is beneficial to improving the stability and cycle performance of lithium-ion batteries under high temperature and fast charging conditions, while also helping to reduce the gas production inside the battery, thereby improving the safety performance of lithium-ion batteries.
[0026] In one embodiment of the present application, and Each independently selected from hydrogen, methyl, ethyl, vinyl,
[0027]
[0028] Any one of .
[0029] It is preferred to control the types of substituents in the crown ether compound within the above range, which is beneficial to improving the complexing ability of the crown ether compound and its compatibility with other components in the electrolyte, and is also beneficial to better adapt to different types of lithium-ion battery systems, thereby improving the overall performance of the battery.
[0030] In one embodiment of the present application, the mass content of the crown ether compound is 1-10% of the total mass of the electrolyte.
[0031] It is preferred to control the mass proportion of the crown ether compound within the above range, which is not only beneficial to improving the complexing effect, but also beneficial to reducing the problem of excessive SEI film thickness caused by excessive addition of crown ether compounds, thereby facilitating improving the cycle life of the battery and the stable performance under high voltage.
[0032] In one embodiment of the present application, the mass ratio of the crown ether compound with the structure shown in the above formula I to the crown ether compound with the structure shown in formula II is 5:1 to 1:1.
[0033] By controlling the mass ratio of the crown ether compounds of the structures shown in Formula I and Formula II within the above range, it is beneficial to promote their uniform distribution in the electrolyte and the synergistic effect, thereby improving the overall performance of the battery.
[0034] In one embodiment of the present application, the lithium salt auxiliary agent is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium hexafluoroarsenate, perfluoroalkylsulfonylmethyl lithium and lithium bis(trifluoromethylsulfonyl)imide.
[0035] It is preferred to control the type of lithium salt additive within the above range, which is beneficial to improving the conductivity, electrochemical window and chemical stability of the electrolyte, thereby improving the fast charging performance and cycle stability of the battery.
[0036] In one embodiment of the present application, the electrolyte includes, by mass percentage, 1-10 wt % of a crown ether compound, 1-5 wt % of lithium bis(fluorosulfonyl)imide, 5-15 wt % of LiPF6, 0.01-5 wt % of vinyl sulfate and an organic solvent.
[0037] The electrolyte having the above composition helps to improve the synergistic effect between the components, thereby obtaining the fast charging performance and cycle stability of the battery. Among them, preferably controlling the use of vinyl sulfate (DTD) as an additive and its mass proportion in the electrolyte helps to enhance its synergistic effect with the crown ether compound, thereby further improving the high temperature cycle stability and safety of the battery without affecting the fast charging performance of the battery.
[0038] In order to improve the dispersion uniformity of each component in the electrolyte, in one embodiment of the present application, the above-mentioned organic solvent preferably includes a first solvent and a second solvent, wherein the first solvent is a cyclic carbonate, and the second solvent is a chain carbonate and / or a carboxylate; preferably, the first solvent is propylene carbonate and / or ethylene carbonate; preferably, the second solvent is selected from any one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, propyl propionate, methyl acetate and γ-butyrolactone.
[0039] In order to further improve the synergistic coordination between the first solvent and the second solvent, in one embodiment of the present application, the mass ratio of the first solvent to the second solvent is preferably 1:1-3.
[0040] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte is the electrolyte described above.
[0041] Since the above-mentioned lithium-ion battery is prepared from the electrolyte in the present application, the lithium-ion battery also has high energy density, stable cycle performance and good safety characteristics under high temperature and fast charging conditions.
[0042] In one embodiment of the present application, the above-mentioned positive electrode sheet includes a positive electrode material, and the positive electrode material is lithium manganese iron phosphate.
[0043] Due to the high manganese content in lithium manganese iron phosphate positive electrode materials, Mn is easily released during the cycle. 2+ ions, resulting in battery performance degradation, but in the lithium-ion battery of the present application, since the above-mentioned specific crown ether compound additive is added to its electrolyte, Mn 2+dissolution and migration, which is beneficial to improve the cycle stability and cycle life of the battery under high temperature and fast charging conditions.
[0044] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.
[0045] The crown ether compounds of structural formula I and structural formula II were purchased from the official website of Aladdin Reagent.
[0046] Example 1
[0047] A method for preparing a lithium iron manganese phosphate secondary battery comprises the following steps performed in sequence:
[0048] The structure of the battery cell consists of: positive electrode, negative electrode, and separator; the positive electrode is lithium iron manganese phosphate positive electrode; the negative electrode is graphite; the formula of the slurry used is the positive electrode material lithium iron phosphate, the conductive agent SuperP, the carbon nanotube (CNT) and the adhesive PVDF in a mass ratio of 95.8:1:0.7:2.5; the above components are assembled according to the conventional preparation method of the battery cell to obtain a battery cell with a capacity of 10Ah.
[0049] The electrolyte solution is composed of: 3 wt% of the crown ether compound of formula I (wherein and -H and -H respectively), 1wt% of the crown ether compound represented by formula II (wherein and -H and -H respectively), 1wt% lithium bis(fluorosulfonyl)imide LiFSI, 12.5wt% LiPF6, 1wt% vinyl sulfate (DTD), and the remainder is a non-aqueous organic solvent; the non-aqueous organic solvent is vinyl carbonate (EC) and ethyl methyl carbonate (EMC), which are mixed in a volume ratio of 1:3.
[0050] Example 2
[0051] The difference from Example 1 is that the electrolyte comprises 2 wt % of the crown ether compound of Formula I and 2 wt % of the crown ether compound of Formula II, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.
[0052] Example 3
[0053] The difference from Example 1 is that the electrolyte comprises 3.33 wt % of the crown ether compound represented by Formula I and 0.67 wt % of the crown ether compound represented by Formula II, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.
[0054] Example 4
[0055] The difference from Example 1 is that the electrolyte comprises: 1 wt % of the crown ether compound represented by Formula I and 3 wt % of the crown ether compound represented by Formula II, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.
[0056] Example 5
[0057] The difference from Example 1 is that the electrolyte comprises: 0.75 wt % of the crown ether compound represented by Formula I, 0.25 wt % of the crown ether compound represented by Formula II, and the remaining ingredients are the same as those in Example 1, and finally a lithium ion battery is obtained.
[0058] Example 6
[0059] The difference from Example 1 is that the electrolyte comprises: 7.5 wt % of the crown ether compound represented by Formula I, 2.5 wt % of the crown ether compound represented by Formula II, and the remaining ingredients are the same as those in Example 1, and a lithium ion battery is finally obtained.
[0060] Example 7
[0061] The difference from Example 1 is that the electrolyte comprises: 10 wt % of the crown ether compound represented by Formula I, 3 wt % of the crown ether compound represented by Formula II, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.
[0062] Example 8
[0063] The difference from Example 1 is that the electrolyte is composed of: 4 wt% of the crown ether compound shown in Formula I (wherein and -H and -OH respectively), 2wt% of the crown ether compound shown in formula II, 2wt% of lithium bis(fluorosulfonyl)imide LiFSI, 15wt% of LiPF6, and the remaining ingredients are the same as the electrolyte in Example 1, and finally a lithium ion battery is obtained.
[0064] Example 9
[0065] The difference from Example 1 is that the electrolyte is composed of: 4 wt% of the crown ether compound shown in Formula I (wherein and -H and -OH respectively), 1wt% of the crown ether compound represented by formula II (wherein and -H and -OH respectively), 4wt% of lithium bis(fluorosulfonyl)imide LiFSI, 10wt% of LiPF6, and the remaining ingredients are the same as the electrolyte in Example 1, and finally a lithium ion battery is obtained.
[0066] Example 10
[0067] The electrolyte includes 1wt% of a crown ether compound, 3wt% of lithium bis(fluorosulfonyl)imide, 10wt% of LiPF6, 0.5wt% of vinyl sulfate, and the rest is an organic solvent.
[0068] Embodiment 11
[0069] The electrolyte includes 10 wt % of a crown ether compound, 5 wt % of lithium bis(fluorosulfonyl)imide, 15 wt % of LiPF6, 2 wt % of vinyl sulfate, and the rest is an organic solvent.
[0070] Example 12
[0071] The electrolyte includes 0.5 wt % of a crown ether compound, 0.5 wt % of lithium bis(fluorosulfonyl)imide, 8 wt % of LiPF6, 1 wt % of vinyl sulfate, and the rest is an organic solvent.
[0072] Embodiment 13
[0073] The difference from Example 1 is that no diethyl sulfate (DTD) is added to the electrolyte, and a lithium ion battery is finally obtained.
[0074] Embodiment 14
[0075] The difference from Example 1 is that ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1 to finally obtain a lithium ion battery.
[0076] Embodiment 15
[0077] The difference from Example 1 is that ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:2 to finally obtain a lithium ion battery.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that no crown ether compound is added to the electrolyte, and a lithium ion battery is finally obtained.
[0080] Comparative Example 2
[0081] The difference from Example 1 is that the crown ether compound in the electrolyte does not contain sulfur, and is 3 wt % of 12-crown 4-ether and 1 wt % of 2-(hydroxymethyl)-12-crown 4-ether, and a lithium ion battery is finally obtained.
[0082] Comparative Example 3
[0083] The difference from Example 1 is that the crown ether compound in the electrolyte contains only 4 wt % of the crown ether compound represented by Formula I, and a lithium ion battery is finally obtained.
[0084] Comparative Example 4
[0085] The difference from Example 1 is that the crown ether compound in the electrolyte contains only 4 wt % of the crown ether compound represented by Formula II, and a lithium ion battery is finally obtained.
[0086] Performance Testing
[0087] Lithium-ion battery high temperature performance test
[0088] The high temperature cycle retention rate and DCR performance tests were performed on the lithium ion batteries in the examples and comparative examples, and the test methods were as follows:
[0089] High temperature cycle performance: At 45°C, the lithium-ion battery is first charged at a constant current of 1C to the upper voltage limit, then charged at the upper voltage limit to a current of 0.05C, and then discharged at a constant current of 1C to the lower voltage limit. The charge and discharge test is performed 1000 times, and the discharge capacity of the 1000th cycle is detected.
[0090] Capacity retention rate = (1000th discharge capacity / first discharge capacity) × 100%.
[0091] Gas production and electrode condition after formation: Confirm the gas production after formation, then disassemble the battery after full charge to confirm the electrode condition of the battery.
[0092] Fast charge cycle stability test: At 25°C, 4C charging and 1C discharging test conditions, each battery sample was charged and discharged between 2.75V and 4.25V. The first cycle test result was used as the capacity 100% benchmark. Each sample was cycled 1000 times, and the capacity retention rate (%) after 1000 cycles was obtained.
[0093] Table 1
[0094]
[0095]
[0096] Among them, it should be noted that "serious gas production" means that the gas production of the battery cell is greater than or equal to 10% of the battery cell volume, which means that during the high-temperature storage process, the manganese ions in the positive electrode are severely dissolved, and the manganese ions and the electrolyte undergo violent side reactions. At the same time, they pass through the diaphragm to gather at the negative electrode, deteriorating the SEI on the negative electrode surface.
[0097] “Low gas production” means that the gas production of the battery cell is less than or equal to 5% of the battery cell volume, indicating that the substances in the electrolyte formula used can complex manganese ions and stabilize the solid electrolyte membrane of the positive and negative electrodes.
[0098] “High gas production” means that the gas production of the battery cell is between 5% and 10% of the battery cell volume, indicating that the electrolyte does not significantly improve the high temperature performance.
[0099] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0100] The electrolyte in the present application uses a thiocrown ether compound with a specific structure as an additive, especially a crown ether compound with a structure shown in Formula I and Formula II. 2+ The sulfur atoms in the thiacrown ethers react with the manganese ions in the electrolyte to form S-Mn bonds, thereby reducing the Mn 2+ The energy barrier overcome when passing through the thiacrown ether ring cavity can not only stabilize the Mn 2+ ions, and can also react with Mn at the interface with the positive electrode. 2+ ions form a stable complex, thereby fundamentally inhibiting the Mn 2+ The ions dissolve and migrate to the negative electrode under high temperature and fast charging conditions, further reducing their damage to the SEI film. According to the hard-soft acid-base theory, the introduction of sulfur atoms can enhance the selective response of crown ether compounds to transition heavy metal ions, and the number of sulfur atoms in the crown ether compounds plays a decisive role in their selectivity. The size of the ring cavity of the crown ether compound also has a certain influence on the selectivity and sensitivity of the crown ether ring. Specifically, the crown ether compound shown in Formula I has two oxygen atoms and two sulfur atoms substituted, and the crown ether compound shown in Formula II has four sulfur atoms substituted. The two have ring cavities of similar size and can synergistically react with Mn with different valence states. 2+ With Mn 3+ ions match, so that the crown ether compound shown in formula I helps to improve the fast charging performance of lithium ion batteries, and the crown ether compound shown in formula II helps to improve the high temperature electrical performance of lithium ion batteries. Through the synergistic effect of the crown ether compounds of the above two structures, a lithium ion battery that can take into account both high temperature electrical performance and fast charging performance is obtained. In addition, the crown ether compound of the above structure allows it to be combined with Li + Ions maintain a certain distance and do not affect Li + The solvation structure of the battery will not reduce the ionic conductivity and fast charging performance of the battery. Therefore, the introduction of the crown ether compound is beneficial to improving the stability and cycle performance of lithium-ion batteries under high temperature and fast charging conditions, while also helping to reduce the gas production inside the battery, thereby improving the safety performance of lithium-ion batteries.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte includes an organic solvent, a lithium salt additive, LiPF6 and an additive, wherein the additive includes a crown ether compound, and the crown ether compound includes structures shown in Formula I and Formula II. Wherein, L1, L2, L3 and L4 are each independently selected from any one of a single bond, a C1-C4 alkylene group and a phenylene group; R1, R2, R3 and R4 are each independently selected from any one of hydrogen, vinyl, amino, cyano, C1-C4 alkyl, five-membered heterocyclic group, phosphate and -C(O)R, and R is selected from any one of hydrogen, hydroxyl and C1-C4 alkyl.
2. The electrolyte according to claim 1, characterized in that and Each independently selected from hydrogen, methyl, ethyl, vinyl, Any one of .
3. The electrolyte according to claim 1 or 2, characterized in that The mass content of the crown ether compound is 1-10% of the total mass of the electrolyte.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The mass ratio of the crown ether compound with the structure shown in formula I to the crown ether compound with the structure shown in formula II is 5:1 to 1:
1.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The lithium salt auxiliary agent is selected from any one or more of lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, lithium hexafluoroarsenate, perfluoroalkylsulfonylmethyl lithium and lithium bis(trifluoromethylsulfonyl)imide.
6. The electrolyte according to claim 5, characterized in that In terms of mass percentage, the electrolyte includes 1 to 10 wt % of the crown ether compound, 1 to 5 wt % of the lithium bis(fluorosulfonyl)imide, 10 to 15 wt % of the LiPF6, 0.5 to 2 wt % of vinyl sulfate and an organic solvent.
7. The electrolyte according to claim 6, characterized in that The organic solvent comprises a first solvent and a second solvent, wherein the first solvent is a cyclic carbonate, and the second solvent is a chain carbonate and / or a carboxylate; Preferably, the first solvent is propylene carbonate and / or ethylene carbonate; Preferably, the second solvent is selected from any one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, propyl propionate, methyl acetate and γ-butyrolactone.
8. The electrolyte according to claim 7, characterized in that The mass ratio of the first solvent to the second solvent is 1:1-3.
9. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The electrolyte solution is the electrolyte solution according to any one of claims 1 to 8.
10. The lithium-ion battery according to claim 9, wherein the positive electrode sheet comprises a positive electrode material, characterized in that: The positive electrode material is lithium manganese iron phosphate.
Citation Information
Cited By
Composite positive electrode material, preparation method thereof and secondary battery
CN120878809A